PROSES GARAPAN DAN PERWUJUDAN KARYA TARI TALEQ - Budi Iman Gunawan; Kawi; Ria Dewi Fajaria (STKIP PGRI BANJARMASIN, 2021)
Taleq in the creation of this work has the meaning of Oath. Inspired by the tradition of taking a student's oath to his teacher to follow the rules in Cimande Pencak Silat. The author interprets the event of the violation of one of the oaths made by a student and he bears bad consequences. The working method uses dramatic and traditional elements. Supported by the method of interview, observation, literature study, and documentation. Cultivation process through the stages of exploration, evaluation and composition. Taleq dance is a group dance which is divided into three scenes with four dancers. Based on the movements of pencak silat, Sundanese traditions, and realist movements that have been modified according to the story. Hanjuang leaves as a sacred symbol in the oath is the hallmark of this work. the use of open space as a performance space in the form of a home page that functions as a setting for a pencak silat practice room. Using makeup and clothing that is based on the cultural character of the Sundanese people. Lighting serves as lighting, strengthening the atmosphere and highlighting the dancer's character. Keywords: Taleq, Oath. Pencak Silat, Traditional Martial Arts.